Islamisasi di Mataram Islam: Historiografi Haji dan Perlawanan Terhadap Kaum Kolonial - Abror, Slamet Miftahul (Tanjak: Sejarah dan Peradaban Islam, 2023)
Hajj trips from time to time have increased both in terms of the number of pilgrims and the facilities obtained. Hajj is an annual worship of Muslims and Muslims around the world flock to the holy land to carry it out. The spirit and tradition of this year has been taught in Islam and has even become part of the pillars of Islam. The pilgrimage during the colonial period presented its own challenges for those who would go to the holy land. The challenge was like having to pay the colonialists, they were also suspected of being a group that would rebel. However, the haj also played a role in spreading the teachings of Islam in Indonesia in general and in the interior of Java in particular. So this article will look at the Hajj in the colonial period and the spread of Islam in Java. This research is library research with qualitative method. The results of the study show that the Hajj in the colonial period and now discusses the differences. This is because during the colonial period, Indonesia was not free to arrange hajj trips. But the pilgrims at that time during the pilgrimage also studied religious knowledge in the holy land. So that when they return to their homeland, they can become scholars and carry out Islamic da'wah in the homeland.